Profilin is a marker of severity in allergic respiratory diseases. Issue 4 (7th January 2020) - Ruiz‐Hornillos, Javier; López‐Matas, M. Angeles; Berges Jimeno, Pilar; Henríquez, Aythamy; Blanco, Sandra; Seoane‐Rodríguez, Marta; Mahíllo, Ignacio; Carnés, Jerónimo
Abstract: Background: The capacity of profilin to induce allergic symptoms in patients with respiratory allergy has been questioned. In this sense, the aim of this study was to investigate the correlation between profilin exposure and induction of symptoms in a prospective case‐control study. Methods: The concentration of profilin as well as pollen levels in the air was measured. A diary score of symptoms was collected from allergic patients. Seventy‐nine individuals were included in the study; fifty cases and 28 controls were positive or negative to profilin, respectively. Conjunctival and bronchial provocation tests were performed with purified profilin (Pho d 2) in a subgroup of cases and controls. Results: Profilin was detected in the environment on 133 days (maximum peak of 0.56 ng/m 3 ). A positive correlation between profilin and pollen count of Olea and Poaceae was observed (ρ = 0.24; P < .001). Intensity of total, nasal and ocular symptoms was statistically higher in cases than in controls ( P < .001). The risk of suffering symptoms, measured by the percentage of patients who presented any of the symptoms each day, was also higher in cases than in controls. The provocation test was positive in 95% of bronchial and 90% of conjunctival challenges in cases, and negative in all controls. Conclusions: Profilin was detected in the environment and had the ability to induce a specific allergen response. Patients sensitized to this panallergen showed more symptoms and were more likely to have symptoms. Therefore, sensitization to profilin seems to be a marker of severity in patients with rhinoconjunctivitis and asthma mediated by pollen. Abstract : Profilin is detected in the environment and has the capacity to induce a specific allergen response as evidenced by bronchial and conjunctival challenges. Patients sensitized to profilin showed more and severe allergic symptoms and had more probability to develop allergic symptoms than the allergic control population negative to profilin. Sensitization to profilin seems to be a marker of severity in pollen allergic patients with rhinoconjunctivitis and asthma.